Analyzing Early Childhood Fairy Tales: Looking for Studies on the Local Wisdom of Madurese Society - Latif, Muhammad Abdul; Pratiwi, Eriqa; Prameswari, Aldila (Al-Athfal: Jurnal Pendidikan Anak, 2024)
Purpose – Moral degradation continues to persist in Indonesia, with various cases of violence and conflicts occurring from early childhood to adolescence. The low foundation of character education is a major issue, especially in early childhood education. This research aims to analyze Bangkalan fairy tales in preserving Madura's local wisdom. Design/methods/approach – The research method employed is qualitative research, utilizing data collection through observation, interviews, and documentation. The research subjects consist of cultural figures in Bangkalan and the folktales from Bangkalan. Data analysis in this research employs thematic analysis with validity testing through source triangulation and technique triangulation. Findings – The findings of this research reveal that the local wisdom embedded in Bangkalan's folktales emphasizes the early cultivation of character traits. These character traits include respect for elders, adherence to religious practices, honesty, and empathy towards others. The research findings provide an alternative approach to instilling local wisdom in early childhood as a foundational framework for children in coping with technological advancements. Research implications/limitations – This research is limited to the analysis of fairy tales intended for early childhood as a means to preserve local wisdom from an early age. Additionally, the research is confined to the cultural context of Bangkalan and may not be applicable to other regions. Future studies could explore similar analyses in different cultural contexts to provide a broader understanding of how fairy tales can preserve local wisdom across various societies. Practical implications – This research provides implications in the form of practices of struggle and nurturing through fairy tales in Bangkalan. It demonstrates how these tales can be used as practical tools for teaching young children about resilience and care, instilling important cultural values from an early age. Originality/value – This research provides positive value for young children by preserving the values of struggle found in Bangkalan fairy tales, contributing to the cultural education and heritage of Madura. By integrating these tales into early childhood education, it helps foster a sense of cultural identity and continuity among the younger generation. Paper type Case study